The Dominance of Coalitions and the Weakening of the Opposition: Implications for the Principle of Checks and Balances Post-2019 Election - Frenki, Frenki; Pradikta, Hervin Yoki (Universitas Islam Negeri Raden Intan Lampung, 2024)
Indonesia, as a democratic state, requires the existence of an opposition to perform the functions of oversight, control, and criticism of the government. However, political realities reveal that many party elites prefer to form coalitions by placing their trusted allies in the cabinet rather than serving as the opposition. This study examines the state of coalitions and opposition in parliament following the 2019 General Election and their implications for the principle of checks and balances. It employs a normative method with a statutory and conceptual approach, analyzing secondary data comprising primary, secondary, and tertiary legal materials descriptively. The findings indicate that major political parties that previously acted as opposition during the 2019 General Election joined the government coalition. This situation strengthened the government's position in formulating policies with minimal resistance. Conversely, the opposition seized this opportunity to secure positions within the government. Although the principle of checks and balances continues to function post-2019, it has proven ineffective due to the limited number of opposition parties. Consequently, government-proposed legislation is frequently passed without significant debate in parliament. This reality negatively impacts Indonesia's democracy, reducing the effectiveness of oversight over executive power. The study concludes that the dynamics of coalitions and opposition post-2019 General Election have weakened the principle of checks and balances, ultimately jeopardizing the quality of democracy in Indonesia.